Fundamental of Entrepreneurship (ENT 300) : RSS Baroqah Enterprise / Mohd Haziq Najmi Zailani ... [et al.] - Zailani, Mohd Haziq Najmi; Jamel, Nur Shuhadah; Zaidi, Zawanah; Mustafa, Hamizan; Hairol, Nur Barieah (2015)
Marketing is defines as the process by which companies create value for customers and build strong relationships between consumer and producer in order to achieve customer satisfaction. The laundry service is to help to reserve the quality of the clothes. To indicate the journey of RSS BAROQAH ENTERPRISE in term of connection between customers satisfaction, products performance and company marketing strength. To bring RSS BAROQAH with trade name of Sutera Pelangi Dobi to the next level of laundry services which premium in quality, price and also to become next level of commercialize laundry servicer in the world.